Tourism arrival in Africa: An empirical investigation - Alang Ernest Wung; Armand Mboutchouang Kountchou; Roger A. Tsafack-Nanfosso (Annals of Tourism Research Empirical Insights, 2023)
The state of tourism development in Africa is yet growing. To this, certain factors such as generosity, ethnic tension and social support in Africa have been put forth to investigate the state of tourism arrivals in Africa. The objective of this paper is therefore to analyze the generosity of Adult Africans measured in three strands; adults' donations to charity, volunteering time to organizations and adults helping strangers or someone, ethnic tension and social support on Tourism arrivals in Africa. Using a panel of forty-one African countries within the period 2006-2017, we employ the smoothed instrumental variable quantile regression and found that African generosity, ethnic tension and social support contribute to the building of the tourism sector in Africa.
Keywords: 330; Africa; Ethnic tension; Generosity; Social support; Tourism arrival